“Grey-area” export credit: a comparative study - L.C. NEHRT (PSL Quarterly Review, 2013)
For the past several years U.S. exporters of capital equipment and large, turn-key projects have lamented that their competitors in Western Europe and Japan had access to long-term, low-interest rate credit which was not available in the US. They argued that if the U.S. government were to facilitate equivalent types of credit they could significantly increase exports. The credit in question was usually that falling between maturities of 10 and 20 years and between interest rates of 3 and 6 percent. This has come to be referred to as “grey-area” export credit. The present study looks at whether, in fact, U.S. exporters suffered from a lack of this type of export credit.